Effectiveness of Application of HC Portal Application (Human Capital) in Administrative Data Management and Employee Health Services in PT PLN (Persero) Unit Induk Pembangunan Sulawesi - Firdayanti H (Journal AGENCY, 2023)
The purpose of this study is a type of qualitative research with the aim of knowing the Effectiveness of Application of HC Portal Application (Human Capital) in Administrative Data Management and Employee Health Services in PT PLN (Persero) Unit Induk Pembangunan Sulawesi. The source of data in this study uses primary data, namely informants of managers and users of the HC Portal Application, and secondary data in the form of related regulatory documents. Data collection techniques in the study used the interview, observation and documentation methods. Based on the results of research, the existence of the HC portal is very time efficient, minimizes errors in services and transactions, makes it easier for employees to access the portal and easy availability of administrative information, greatly assists employees in uploading health administration data, as well as easy management of employee data. So that in this study the authors can conclude that whereas in general, employees of PT PLN (Persero) Unit Induk Pembangunan Sulawesi as users feel very helpful and more effective than the previous process. This is also felt by YAN HC Makassar employees as managers, because the HC portal is very helpful and facilitates their work process in managing administrative data and serving health services..